Geographic Variation in Radiologist Capacity and Widespread Implementation of Lung Cancer CT Screening. (December 2014) - Smieliauskas, Fabrice; MacMahon, Heber; Salgia, Ravi; Shih, Ya-Chen Tina
Background: Newly released United States Preventive Services Task Force (USPSTF) recommendations for lung cancer screening are expected to increase demand for low-dose computed tomography scanning, but health system capacity constraints might threaten the scale-up of screening. Objectives: To estimate the prevalence of capacity constraints in the radiologist workforce and resulting potential disparities in access to lung cancer screening. Methods: We combined information from health interview surveys to estimate the numbers of smokers who meet the USPSTF eligibility criteria, and information from administrative datasets to estimate the numbers of radiologists and the numbers of scans they currently interpret in Health Service Areas (HSAs) nationwide. We estimated and mapped the prevalence of capacity constrained HSAs – those having a greater than 5% or greater than 25% projected increase in scans over current levels from scaling up screening – and used descriptive statistics and logistic regressions to identify HSA characteristics associated with capacity constraints. Results: Scaling up lung cancer screening would increase imaging procedures by an average of 4% across HSAs. Of the 9.6 million eligible smokers, 1, 023, 943 lived in HSAs with increases of at least 5%. HSAs that were rural, with many eligible smokers, and disproportionately Hispanic or low-income smokers had significantly higher odds of facing capacity constraints. Conclusions: Disparities in access to lung cancer screening appear likely unless policy makers target HSAs with few radiologists for additional resources. Radiologists should be able to absorb the workload imposed by lung cancer screening in most areas of the country.